Sociοeconomic and environmental inequalities between the regions of the European countries in times of economic crisis: An empirical comparative analysis - Avrami, Lydia (The Greek Review of Social Research, 2019)
This study aims to empirically investigate within-country social and environmental inequalities in EU Member States in times of economic crisis. To this end, we conduct the comparative analysis of the interregional deviations in 19 EU Member States in 2013, focusing on the exposure of the regional population to the air pollution and its socio-economic status. A cross-sectional time-series analysis of the regions of seven European countries over the period 2009-2013 is carried out in order to explore the association between the exposure to air pollution and the socio-economic status of the regional population. The analysis demonstrates the significant social and environmental inequalities in the majority of European countries. Even though, the socially equitable distribution of environmental quality between European regions emerged, in some European countries already socially vulnerable groups are exposed to disproportionally high air pollution levels and, consequently, they are more susceptible to climate change effects, especially in times of crisis.